7 Genetic Variants in the Vascular Endothelial Growth Factor Pathway As Potential Markers of Ovarian Cancer Risk, Therapeutic Response, and Clinical Outcome. (11th January 2018) - Cao, Liyun; Ma, Zhan; Meng, Qing
Abstract: Background: As a key regulator of angiogenesis, vascular endothelial growth factor (VEGF) plays an important role in physiology of normal ovaries and pathogenesis of ovarian cancer, such as tumorigenesis and metastasis. The objective of this study was to assess the association of genetic variants in the VEGF pathway with ovarian cancer risk, therapeutic response, and survival. Patients and Methods: A cohort of 339 ovarian cancer patients matched with 349 healthy controls by age, gender, and ethnicity were tested for single nucleotide polymorphisms (SNPs) in VEGF and VEGF receptor (VEGFR) genes using the Illumina iSelect platform. The statistical analyses were performed using Intercooled STATA software. P value ≤ .05 was considered significant. The overall risk of ovarian cancer and likelihood of poor treatment response were estimated as odds ratios (ORs) with 95% confidence intervals (CIs) for each SNP using unconditional multivariate logistic regression. The overall risk of death was estimated as hazard ratios (HRs) and 95% CIs for each SNP using the Cox proportional hazards model. Results: Sixteen SNPs from five genes in the VEGF-VEGFR axis were identified as significantly associated with an increased risk of ovarian cancer, among which VEGFR-3 rs6877011 showed the highest risk of ovarian cancer (OR 1.66, 95% CI 1.09–2.53), while VEGFR-1 rs11149523 showed the lowest risk (OR 0.51, 95% CI 0.32–0.83). Ten SNPs from four genes were identified as significantly associated with platinum-based chemotherapeutic response, among which VEGFR-2 rs1531289 was associated with a favorable treatment response (OR 0.64, 95% CI 0.42–0.98), and all the other variants showed a significant association with a poor chemotherapeutic response. In particular, VEGFR-1 rs8000288 showed the highest risk of poor chemotherapeutic response (OR 4.25, 95% CI 1.10–16.43). Twelve SNPs from four genes were identified as significantly associated with the overall survival of ovarian cancer patients, among which fms like tyrosine kinase 3 (Flt3) rs3003955 was the most significant variant associated with improved prognosis (HR 0.59, 95% CI 0.41–0.84), while VEGFR-1 rs17626553 was the most significant one associated with poor prognosis (HR 4.07, 95% CI 1.86–8.92). Conclusions: Multiple genetic variants in the VEGF pathway significantly associated with ovarian cancer risk, therapeutic response, and survival are identified in our study. These findings may provide a potential molecular approach for ovarian cancer risk assessment, patient management and clinical outcome prediction.